Managing Parrot Bite Injuries to the Hand: Not Just Another Animal Bite. (March 2015) - King, I. C. C.; Freeman, H.; Wokes, J. E.
Bites and scratches are common injuries, frequently sustained from humans, dogs and cats. Exotic pet-related harm however is an important and increasingly emerging class of injury. Whilst the principles of prompt and thorough medical assessment, antibiotics and potential surgical washout and debridement apply, exotic pet wounds require further consideration. Standard antibiotic prophylaxis with amoxicillin/clavulanic acid (also known as co-amoxiclav) is not sufficient for the pathogens transmitted by parrot bites. We illustrate the importance of adequate consideration of microbiological pathogens with a case report of an open finger fracture resulting from a parrot bite. We intend this to be a valuable resource for healthcare professionals in their effective management of such injuries. Level of Evidence: V